Latest Results from Proto-MPEX and the Future Plans for MPEX. (3rd October 2019) - Rapp, J.; Lumsdaine, A.; Beers, C. J.; Biewer, T. M.; Bigelow, T. S.; Caneses, J. F.; Caughman, J. B. O.; Goulding, R. H.; Kafle, N.; Lau, C. H.; Lindquist, E.; Piotrowicz, P. A.; et al.
Abstract: The Prototype Material Plasma Exposure eXperiment (Proto-MPEX) is being used to qualify the plasma source and heating systems for the Material Plasma Exposure eXperiment (MPEX). The MPEX will address important and urgent research needs on plasma material interactions for future fusion reactors. In MPEX, plasma-facing components (nonirradiated and a priori neutron irradiated) will be exposed to plasma conditions as they are expected in future fusion reactors. The MPEX, a steady-state device enabled by superconducting magnets, will be able to break into new ground by assessing plasma-facing materials and components at an ion fluence level in the range of 10 30 to 10 31  m −2 . To achieve the relevant plasma conditions, high-density plasmas (>4 × 10 19  m −3 ) are produced with a high-power helicon source. The so-produced low-temperature helicon plasma is then additionally heated with waves in the ion cyclotron resonance frequency and electron cyclotron resonance frequency domains. Proto-MPEX has achieved all key parameters (source ne, source Te, source Ti, target Te, target Ti, target ion flux, and target heat flux) within a factor of 2 of the design requirements of MPEX, albeit not simultaneously. These parameters were achieved with a total installed heating power of 330 kW, which is less than half of the planned heating power in the MPEX (800 kW). An overview of the latest results from Proto-MPEX is given. These results are shown in relationship to the MPEX system goals. Remaining necessary research and development tasks are discussed. The MPEX is currently in the conceptual design phase. The status of the design and an overview of the system requirements are presented.